Spectroscopic study on appearances of make‐up skins using a visible RGB‐LED OCT. Issue 3 (24th March 2014) - Tsugita, Tetsuya; Kimura, Ryouta; Iwai, Toshiaki
<x xml:space="preserve">Abstract</x> Background/purpose Facial foundation is very effective to correct color irregularities of the skin surface and to protect the skin from harmful light. This depends strongly on both the optical properties and the coating condition of foundation on the skin surface. Methods We constructed the full‐field optical coherence tomography (OCT) (FF‐OCT) microscope with visible light sources of RGB LEDs. The commercially available skin replicas were used as the model of skin in the experiment, which were composed of two layers, a thin polyurethane film transcribed from cheek surface of a female and a beige‐colored silicone substrate. The foundations were applied to the skin replicas under the constant pressure. Results A topographic image provides spectroscopic information of reflected light and effectiveness of correction of surface irregularities by applying the foundation. A tomographic image demonstrates the spectroscopic degree of light penetration into the skin tissue. It is shown that the reflectivity increases consistently with thickness of the applied foundation because light reflected from the surface and diffusively reflected from the inside of the tissue increases as the surface becomes flat applying the foundation. Conclusion We confirmed experimentally the potential of the spectroscopic FF‐OCT microscopy in investigating both qualitatively and quantitatively the effectiveness of facial foundation.